Kingdom of the wicked ebook - Maniscalco, Kerri (Kingdom of the Wicked, 2020)
A James Patterson Presents Novel   From the #1 New York Times and USA Today bestselling author of the Stalking Jack the Ripper series comes a new blockbuster series...   Two sisters. One brutal murder.   A quest for vengeance that will unleash Hell itself...   And an intoxicating romance.  Emilia and her twin sister Vittoria are streghe — witches who live secretly among humans, avoiding notice and persecution. One night, Vittoria misses dinner service at the family's renowned Sicilian restaurant. Emilia soon finds the body of her beloved twin...desecrated beyond belief. Devastated, Emilia sets out to find her sister's killer and to seek vengeance at any cost-even if it means using dark magic that's been long forbidden. Then Emilia meets Wrath, one of the Wicked-princes of Hell she has been warned against in tales since she was a child. Wrath claims to be on Emilia's side, tasked by his master with solving the series of women's murders on the island. But when it comes to the Wicked, nothing is as it seems...